Introduction of interactive forms of learning as a means of formation of the linguistic personality of foreign students - Chernovol, O.; Черновол, Ольга Григорівна (Osaka : CPN Publishing Group, 2020)
The article discusses the issues of intensification of the learning process through the introduction of interactive forms of learning as a means of formation of the linguistic personality of foreign students, as well as describes the methodological peculiarities of their use in the study of Ukrainian as a foreign language. The introduction of interactive forms of education in the system of university education improves its quality in accordance with the needs of society and the individual.
Keywords: interactive forms of learning; linguistic personality; interlingual communication; introduction; Ukrainian as a foreign language